2022
DOI: 10.1111/bph.15994
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric activation of microglia in the hippocampus drives anxiodepressive consequences of trigeminal neuralgia in rodents

Abstract: Background and Purpose Patients suffering from trigeminal neuralgia are often accompanied by anxiety and depression. Microglia‐mediated neuroinflammation is involved in the development of neuropathic pain and anxiodepression pathogenesis. Whether and how microglia are involved in trigeminal neuralgia‐induced anxiodepression remains unclear. Experimental Approach Unilateral constriction of the infraorbital nerve (CION) was performed to establish trigeminal neuralgia in rat and mouse models. Mechanical allodynia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…We previously showed that TN mice exhibit obvious anxiodepressive-like behaviors by 14 days but not 4 day after chronic constriction injury of the infraorbital nerve (CION), indicating that anxiodepressive-like behaviors caused by neuropathic pain were time dependent ( 21 ). In this study, we investigated whether TN altered the excitability and synaptic transmission of mPFC neurons accompanying the anxiodepressive-like behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that TN mice exhibit obvious anxiodepressive-like behaviors by 14 days but not 4 day after chronic constriction injury of the infraorbital nerve (CION), indicating that anxiodepressive-like behaviors caused by neuropathic pain were time dependent ( 21 ). In this study, we investigated whether TN altered the excitability and synaptic transmission of mPFC neurons accompanying the anxiodepressive-like behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…S4, A to G). Our previous study showed that inhibition of microglia in the ipsilateral but not the contralateral dorsal hippocampus (dHPC) blocked CION-induced anxiodepressive-like behaviors, suggesting an asymmetric role of dHPC ( 21 ). However, unlike manipulating dHPC microglia, there was no significant difference in the anti-anxiodepressive effects of silencing ipsilateral and contralateral vHPC CaMK2A + neurons (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with previous studies, in this research, the injury of hippocampal structure and function exhibited depressive-like behaviors, as evidenced SPT, TST, and NSFT tests. Additionally, the deficiency in hippocampal activity is required for anxiety-like behaviors ( Chen et al, 2022 ; Scholl et al, 2022 ). Some studies reported by other groups have indicated that anxiety-like behaviors could be generated through ischemic/reperfusion injury ( Jin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%